Halogen-free epoxy resin composition, prepreg, metal foil-clad laminate and printed circuit board containing the same
By adding a wetting dispersant to the halogen-free epoxy resin composition, the dispersion effect of boron nitride is improved, and the problem of insufficient thermal conductivity and heat resistance in the prior art is solved, and a halogen-free epoxy resin composition with high thermal conductivity, strong peelability and good dielectric properties is achieved.
Patent Information
- Application Number
- CN202411993833.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing halogen-free low-dielectric materials have shortcomings in thermal conductivity and heat resistance, and poor dispersion of boron nitride in the resin mixture leads to increased viscosity, reduced copper foil peel strength and abnormal internal mass of the substrate.
By adding a wetting dispersant to the halogen-free epoxy resin composition, the dispersion effect of boron nitride in the resin system is improved, the viscosity and minimum melt viscosity are reduced, and the thermal conductivity and peel strength are improved.
Without deteriorating dielectric properties, the thermal conductivity and peel strength of the sheet are improved, the internal quality problems of the substrate caused by poor boron nitride dispersion are solved, and the overall heat resistance and glass transition temperature are improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of laminated boards, and relates to a halogen-free epoxy resin composition, a prepreg containing the same, a metal foil-clad laminated board and a printed circuit board. Background Art
[0002] As electronic products develop towards being thinner and more integrated, the demand for both thermal conductivity and dielectric properties is increasing. Conventional halogen-free low-dielectric materials are basically a combination of epoxy resin and silicon micropowder filler, which do not have sufficient thermal conductivity. Boron nitride is currently commonly used in copper clad laminates to improve thermal conductivity. Boron nitride has a low thermal expansion coefficient, low dielectric constant and high thermal conductivity, and its application will become more and more extensive.
[0003] Boron nitride has many advantages, but boron nitride is a smooth flaky structure. If it is directly applied to a resin mixture, the viscosity will increase significantly, the glue flow ability of the bonding sheet will be weakened during the lamination process, and the copper foil peel strength of the plate will be reduced. The problem leads to poor heat resistance of the plate, and there will be problems with abnormal quality inside the substrate. The industry has tried to blend boron nitride with a wetting dispersant to improve the dispersibility of boron nitride in the resin mixture. However, due to the thermal decomposition of the wetting dispersant and the presence of polar groups, the heat resistance of the copper clad laminate will be reduced and the dielectric properties will be increased. Therefore, the development of a resin composition with excellent thermal conductivity, heat resistance and dielectric properties and high peel strength is a problem that needs to be solved in this field. Summary of the invention
[0004] In view of the deficiencies of the prior art, the object of the present invention is to provide a halogen-free epoxy resin composition, a prepreg comprising the same, a metal foil-clad laminate and a printed circuit board.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In one aspect, the present invention provides a halogen-free epoxy resin composition, comprising the following components in parts by weight:
[0007] Epoxy resin: 100 parts by weight; low dielectric curing agent: 10-75 parts by weight; boron nitride: 40-100 parts by weight; phosphorus-containing flame retardant: 20-50 parts by weight; and a wetting and dispersing agent;
[0008] The addition amount of the wetting and dispersing agent is 1%-5% of the weight of the boron nitride; the difference between the acid value and the amine value of the wetting and dispersing agent does not exceed 10 mgKOH / g, and the molecular weight Mw is 10000-20000.
[0009] In the present invention, by adding a wetting dispersant, the dispersion effect of boron nitride in the resin system can be improved without deteriorating the dielectric properties, the viscosity and the minimum melt viscosity of the resin system can be reduced, and the thermal conductivity of the board can be improved. At the same time, since the wetting dispersant contains an amino group, the peel strength of the board can also be improved. Moreover, since the dispersibility of boron nitride in the resin system is improved and the minimum melt viscosity is reduced, the uniformity of the adhesive flow of the bonding sheet during the lamination process can be effectively improved, thereby solving the internal quality problem of the substrate caused by the poor fluidity of boron nitride.
[0010] In the present invention, the molecular weight Mw of the wetting and dispersing agent is 10000, 12000, 14000, 15000, 18000 or 20000. In the present invention, if the weight average molecular weight of the wetting and dispersing agent is lower than 10000, it is easy to volatilize and decompose when it is baked at high temperature during the prepreg manufacturing process, and the improvement effect on the minimum melt viscosity is not great; if the molecular weight is higher than 20000, its ability to promote the dispersion of boron nitride becomes weak.
[0011] Preferably, the Td (weight loss 5%) of the wetting and dispersing agent is ≥ 220°C, such as 220°C, 225°C, 230°C, 240°C, 250°C, 260°C, 280°C, 300°C, 350°C, 380°C, 400°C, etc. In the present invention, if the Td (weight loss 5%) of the wetting and dispersing agent used is lower than 220°C, the dispersant will decompose during the high-temperature lamination process, weakening its dispersing effect, resulting in poor heat resistance of the board and poor improvement of glass strength.
[0012] Preferably, the acid value and amine value of the wetting and dispersing agent differ by no more than 10 mgKOH / g (e.g., 10 mgKOH / g, 9 mgKOH / g, 8.5 mgKOH / g, 8 mgKOH / g, 7 mgKOH / g, 6 mgKOH / g, 5.5 mgKOH / g, 4 mgKOH / g, 3 mgKOH / g, 2 mgKOH / g, 1 mgKOH / g, 10 mgKOH / g, etc.). If the acid value and amine value of the wetting and dispersing agent used in the present invention differ too much, the dielectric properties of the board will be deteriorated.
[0013] In the present invention, the addition amount of the wetting and dispersing agent can be 1%, 1.5%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5% of the weight of boron nitride. If the addition amount is too low, the dispersion effect is not good, and the improvement effect on the viscosity of the resin system and the minimum melt viscosity is not good; if the addition amount is too large, the heat resistance of the board will be affected.
[0014] Preferably, the epoxy resin is selected from one or a combination of at least two of a bifunctional epoxy resin or a multifunctional epoxy resin.
[0015] Preferably, the epoxy resin is selected from any one or a combination of at least two of bisphenol A epoxy resin, bisphenol F epoxy resin, novolac epoxy resin, phosphorus-containing epoxy resin, dicyclopentadiene epoxy resin, dimethylphenol novolac epoxy resin, tetramethylbiphenyl epoxy resin, biphenyl epoxy resin, MDI-modified epoxy resin, naphthalene ring-containing epoxy resin or alicyclic epoxy resin.
[0016] Preferably, the low dielectric curing agent includes any one of a benzoxazine curing agent, an active ester curing agent, an anhydride curing agent, a phenolic resin curing agent, an amine curing agent, a carboxylic acid curing agent, a cyanate curing agent, a benzoxazine curing agent or a maleimide curing agent, or a combination of at least two thereof.
[0017] Preferably, the benzoxazine resin includes any one of bisphenol A benzoxazine, bisphenol F benzoxazine, bisphenol S benzoxazine resin, DDM benzoxazine resin, ODA benzoxazine resin, phenolphthalein benzoxazine resin or DCPD benzoxazine resin, or a combination of at least two thereof.
[0018] Preferably, the anhydride curing agent is selected from any one or a combination of at least two of the following formula I or formula II:
[0019]
[0020]
[0021] wherein n:x=1:1-8:1 (e.g., 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1 or 8:1);
[0022] Preferably, the active ester curing agent is selected from any one or a combination of at least two of the active esters having the following structure of Formula III or Formula IV:
[0023]
[0024] III wherein X is phenyl or naphthyl, j is 0 or 1, k is 0 or 1, and n represents a repeating unit of 0.25 to 1.25 (e.g., 0.25, 0.50, 0.80, 1.0, 1.1, 1.2 or 1.25);
[0025]
[0026] In IV, m, n, q are independently integers of 1-6 (e.g., 1, 2, 3, 4, 5 or 6), X is phenyl or naphthyl, and Y is the following group:
[0027]
[0028] Where K is 0 or 1.
[0029] In the present invention, relative to 100 parts by weight of epoxy resin, the amount of the low dielectric curing agent can be 10 parts by weight, 13 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight, 50 parts by weight, 55 parts by weight, 60 parts by weight, 65 parts by weight, 70 parts by weight or 75 parts by weight.
[0030] In the present invention, the average particle size of the boron nitride is 2-20 μm, for example, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm or 20 μm.
[0031] In the present invention, relative to 100 parts by weight of epoxy resin, the amount of boron nitride can be 40 parts by weight, 45 parts by weight, 50 parts by weight, 55 parts by weight, 58 parts by weight, 60 parts by weight, 65 parts by weight, 70 parts by weight, 75 parts by weight, 80 parts by weight, 85 parts by weight, 90 parts by weight, 95 parts by weight or 100 parts by weight.
[0032] Preferably, the halogen-free epoxy resin composition further comprises other fillers.
[0033] Preferably, the other filler is selected from any one or a combination of at least two of aluminum hydroxide, composite silica, fused silica, talc, boehmite, zeolite, wollastonite, magnesium oxide, calcium silicate, calcium carbonate, clay or mica.
[0034] Preferably, the other fillers have a median particle size D50 of 1.8-4.4 μm (e.g., 1.8 μm, 2.0 μm, 2.3 μm, 2.5 μm, 2.8 μm, 3.0 μm, 3.2 μm, 3.5 μm, 3.8 μm or 4.4 μm), and a maximum particle size D100 of 5.0-20 μm (e.g., 5.0 μm, 7.0 μm, 10.0 μm, 12.0 μm, 14.0 μm, 15.0 μm, 18.0 μm or 20 μm).
[0035] Preferably, the physical form of the other fillers may be flake-shaped, rod-shaped, spherical, hollow spherical, granular, fibrous or plate-shaped.
[0036] Preferably, the content of other fillers in the halogen-free epoxy resin composition is 40 to 200 parts by weight, for example, 40 parts by weight, 50 parts by weight, 80 parts by weight, 100 parts by weight, 130 parts by weight, 150 parts by weight, 180 parts by weight, 200 parts by weight, 250 parts by weight, 300 parts by weight, 350 parts by weight or 400 parts by weight.
[0037] In the present invention, the phosphorus-containing flame retardant is selected from reactive phosphorus-containing flame retardants and / or additive phosphorus-containing flame retardants;
[0038] Preferably, the reactive phosphorus-containing flame retardant is a compound containing phosphorus element and a reactive group.
[0039] Preferably, the reactive groups include amino groups and / or phenolic hydroxyl groups.
[0040] Preferably, the reactive phosphorus-containing flame retardant comprises a phosphorus-containing phenolic resin.
[0041] Preferably, the additive phosphorus-containing flame retardant includes any one of tri(2,6-dimethylphenyl)phosphine, 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphophananthrene-10-oxide, 2,6-di(2,6-dimethylphenyl)phosphinobenzene, 10-phenyl-9,10-dihydro-9-oxa-10-phosphophananthrene-10-oxide, phosphazene compounds or phosphate esters, or a combination of at least two thereof.
[0042] In the present invention, relative to 100 parts by weight of epoxy resin, the phosphorus-containing flame retardant is added in an amount of 20-50 parts by weight, for example, 20 parts by weight, 26 parts by weight, 28 parts by weight, 30 parts by weight, 35 parts by weight, 38 parts by weight, 41 parts by weight, 43 parts by weight, 45 parts by weight or 50 parts by weight.
[0043] Preferably, the halogen-free epoxy resin composition further comprises a curing accelerator.
[0044] Preferably, the curing accelerator is selected from any one of imidazole accelerators, pyridine curing agents, Lewis acid curing agents, amine curing agents, phenolic curing agents, cyanate compounds or active ester compounds, or a combination of at least two thereof.
[0045] On the other hand, the present invention provides a resin adhesive, which is obtained by dissolving or dispersing the halogen-free epoxy resin composition described above in a solvent.
[0046] Preferably, the solvent is selected from any one of butanone, acetone, DMF, ethylene glycol monobutyl ether, ethylene glycol monomethyl ether, toluene, xylene, cyclohexanone, and isopropanol, or a combination of at least two thereof.
[0047] In the present invention, the solid content of the resin glue is 60-70%, for example, 60%, 63%, 65%, 68% or 70%.
[0048] In another aspect, the present invention provides a prepreg, comprising a base material and the halogen-free epoxy resin composition as described above attached to the base material after being impregnated and dried.
[0049] In another aspect, the present invention provides a metal foil-clad laminate, comprising at least one prepreg as described above and a metal foil coated on one side or both sides of the laminated prepreg.
[0050] In another aspect, the present invention provides a printed circuit board, comprising at least one of the prepreg as described above or the metal foil clad laminate as described above.
[0051] Compared with the prior art, the present invention has the following beneficial effects:
[0052] The present invention can improve the dispersion effect of boron nitride in the resin system without deteriorating the dielectric properties by adding a wetting dispersant, reduce the glue viscosity and the minimum melt viscosity, and improve the thermal conductivity of the plate. At the same time, since the wetting dispersant contains an amino group, the peel strength of the plate can also be improved. Moreover, since the dispersibility of boron nitride in the resin system is improved, the uniformity of the glue flow of the bonding sheet during the lamination process can be effectively improved, thereby solving the problem of abnormal internal quality of the substrate caused by the difficulty of boron nitride to flow. DETAILED DESCRIPTION
[0053] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0054] The materials used in the following examples and comparative examples are as follows:
[0055] Epoxy resin 1: NPEL-128, bisphenol A type epoxy resin, Nan Ya.
[0056] Epoxy resin 2: NPEF-170, bisphenol F type epoxy resin, Nan Ya.
[0057] Epoxy resin 3: BNE200, phenol novolac type epoxy resin, Changchun.
[0058] Curing agent 1: LZ8290, bisphenol A type benzoxazine resin, Huntsman.
[0059] Curing agent 2: SMA-EF40, styrene maleic anhydride copolymer, CrayValley.
[0060] Curing agent 3: DFE-617L, active ester, Sichuan Dongcai.
[0061] Wetting and dispersing agent 1: BYK-2205, BYK Chemical. The difference between the acid value and the amine value (solid content conversion) is 3 mgKOH / g, Mw is 15000, Td (weight loss 5%)>220°C.
[0062] Wetting and dispersing agent 2: BYK-2200, BYK Chemical. The difference between the acid value and the amine value (solid content conversion) is 8 mgKOH / g, Mw is 20000, Td (weight loss 5%)>220°C.
[0063] Wetting and dispersing agent 3: BYK-9076, BYK Chemical. The difference between the acid value and the amine value (solid content conversion) is 6 mgKOH / g, Mw is 10000, and Td (weight loss 5%) is >220°C.
[0064] Wetting and dispersing agent 4: BYK-961, BYK Chemical. The difference between the acid value and the amine value (solid content conversion) is 0 mgKOH / g, Mw is 5000, and Td (weight loss 5%) is <220°C.
[0065] Wetting and dispersing agent 5: BYK-2157, BYK Chemical. The difference between the acid value and the amine value (solid content conversion) is 13 mgKOH / g, Mw is 10000, and Td (weight loss 5%) is >220°C.
[0066] Wetting and dispersing agent 6: BYK-2025, BYK Chemical. The difference between the acid value and the amine value (solid content conversion) is 1 mgKOH / g, Mw is 22000, Td (weight loss 5%)>220°C.
[0067] Wetting and dispersing agent 7: BYK-2001, BYK Chemical. The difference between the acid value and the amine value (solid content conversion) is 10 mgKOH / g, Mw is 10000, and Td (weight loss 5%) is less than 220°C.
[0068] Boron nitride: BN005, Lianrui New Materials.
[0069] Silica: DS1032, Lianrui New Materials.
[0070] Phosphorus-containing flame retardant: Phosphorus-containing phenolic resin XZ92741, Dow, USA.
[0071] Phosphorus-containing flame retardant: Phosphate ester PX200, Japan Daihachi Chemical
[0072] Curing accelerator: 2-ethyl-4-methylimidazole, Shikoku Chemical Co., Ltd., Japan.
[0073] The resin compositions provided in the examples and comparative examples were used to prepare laminates for printed circuits according to the following method, and the performance of the prepared laminates was tested.
[0074] Put the above materials and butanone in a container, stir evenly to make glue, and use butanone to adjust the glue into a glue solution with a solid content of 60%. Use 2116 electronic grade glass fiber cloth to impregnate the glue solution and bake it in an oven to make prepreg;
[0075] Six prepregs are bonded together by heating and pressurizing, and copper foils are placed on the upper and lower surfaces, and smooth steel plates and plastic pads are placed outside the upper and lower copper foils, and laminated boards are pressed in a laminator; wherein, the lamination operating conditions are 80-140°C, the heating rate is controlled at 1.5-2.5°C / min, the outer layer material temperature is 80-100°C, full pressure is applied, the full pressure is about 350psi, during curing, the material temperature is controlled at above 200°C, and the heat is kept for more than 100 minutes to obtain a copper clad laminate.
[0076] Example
[0077] The formulation composition and physical property data of each embodiment are shown in Table 1, and the formulation composition and physical property data of the comparative example are shown in Table 2 and Table 3. The weight parts content in the table refers to the solid weight parts without solvent.
[0078] Table 1
[0079]
[0080]
[0081] Table 2
[0082]
[0083]
[0084] Table 3
[0085]
[0086] As shown in the table above, 2.75E+06 means 2.75×10 6 , and so on for other similar expressions.
[0087] The above performance test method is as follows:
[0088] (1) Copper foil peel strength: Prepare samples of gold-clad copper foil laminates and measure them according to the method specified in IPC-TM-650 2.4.8;
[0089] (2) Thermal conductivity: According to the ASTM D5470 test method, the metal-based copper-clad laminate was prepared into a 25.4 mm × 25.4 mm sample to test the thermal conductivity of the board;
[0090] (3) Dielectric constant (1 GHz): Measured using the parallel plate capacitance method in accordance with the method specified in 2.5.5.9 of IPC-TM-650.
[0091] (4) Melt viscosity: Anton Paar rheometer MCR301 was used to test at a heating rate of 3°C / min. The lowest point of the viscosity curve drawn by the instrument is the lowest melt viscosity of the sample.
[0092] (5) T288: Use a thermomechanical analyzer and measure according to the method specified in IPC-TM-650 2.4.24.1;
[0093] (6) Flammability: measured according to the vertical combustion method of UL-94 standard.
[0094] (7) Internal quality of substrate: The standard method specified in IPC-TM-650 is used to test whether there are dried flowers in the substrate by visual inspection or sectioning.
[0095] From Table 1, in Examples 1-9 of the present application, the copper foil peel strength of the metal copper foil laminate is 0.60-0.83 N / mm, the dielectric constant is less than 4, and the thermal conductivity is 0.81-0.9 W / m·K. The prepared copper clad laminate has a high thermal conductivity, a low dielectric constant, and good overall performance of the board.
[0096] From the perspective of board performance: compared with Examples 1-13, since Comparative Example 1 does not use a wetting and dispersing agent, the board peeling strength and thermal conductivity are relatively low, and there are more dry flowers on the whole board. Comparative Example 2 uses too little wetting and dispersing agent, which has no obvious improvement effect on the reduction of viscosity, and the thermal conductivity of the board is relatively poor, and the substrate has more dried flowers on the whole board; Comparative Example 3 uses too much wetting and dispersing agent, which will cause a certain reduction in the Tg and heat resistance of the board; Comparative Example 4 uses a wetting and dispersing agent with a low molecular weight and Td < 220°C. Due to the low molecular weight and low Td, the wetting and dispersing agent is easy to volatilize and decompose, and has no obvious effect on improving the melt viscosity of the resin system. There are more dried flowers on the whole board, and the Tg and T288 of the board are deteriorated; Comparative Example 5 uses a wetting and dispersing agent with an acid value and an amine value of 13 mgKOH / g. Due to the high acid value and amine value, the dielectric of the board is significantly improved; Comparative Example 6 uses a wetting and dispersing agent with Mw>20000. Due to the large Mw molecular weight, the improvement of the dispersibility of boron nitride is poor, and the reduction of the melt viscosity of the resin system is limited. , which results in the thermal conductivity of the board not being significantly improved; the wetting dispersant Td used in Comparative Example 7 is less than 220°C. Due to the low Td, it is easy to decompose and inactivate during the curing process, and the dispersion effect is weakened, thereby affecting the heat resistance and thermal conductivity of the board. Comparative Examples 8 and 9 use too low and too high amounts of phosphorus-containing flame retardants, respectively. Too low amounts will result in poor flame retardancy and low Tg of the board, and too high amounts will result in poor heat resistance and Tg; Comparative Examples 10 and 11 use too low and too high amounts of low-dielectric curing agents, respectively. Too low amounts of low-dielectric curing agents will improve the dielectric properties of the board and reduce Tg, etc., and too high amounts of low-dielectric curing agents will affect the Tg and heat resistance of the board; Comparative Examples 12 and 13 use too low or too high amounts of boron nitride, respectively. The thermal conductivity of the board with too low an amount does not meet the requirements, and too high an amount, due to the high viscosity, does not significantly improve the thermal conductivity of the board and there are a few dried flowers on the whole board.
[0097] The applicant declares that the present invention illustrates the halogen-free epoxy resin composition and its application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A halogen-free epoxy resin composition, characterized in that The halogen-free epoxy resin composition comprises the following components in parts by weight: Epoxy resin: 100 parts by weight; low dielectric curing agent: 10-75 parts by weight; boron nitride: 40-100 parts by weight; phosphorus-containing flame retardant: 20-50 parts by weight; and a wetting and dispersing agent; The addition amount of the wetting and dispersing agent is 1%-5% of the weight of the boron nitride; the difference between the acid value and the amine value of the wetting and dispersing agent does not exceed 10 mgKOH / g, and the molecular weight Mw is 10000-20000.
2. The halogen-free epoxy resin composition according to claim 1, characterized in that The Td (weight loss 5%) of the wetting and dispersing agent is ≥ 220°C.
3. The halogen-free epoxy resin composition according to claim 1 or 2, characterized in that: The epoxy resin is selected from one or a combination of at least two of a bifunctional epoxy resin or a multifunctional epoxy resin; Preferably, the epoxy resin is selected from any one or a combination of at least two of bisphenol A epoxy resin, bisphenol F epoxy resin, novolac epoxy resin, phosphorus-containing epoxy resin, dicyclopentadiene epoxy resin, dimethylphenol novolac epoxy resin, tetramethylbiphenyl epoxy resin, biphenyl epoxy resin, MDI-modified epoxy resin, naphthalene ring-containing epoxy resin or alicyclic epoxy resin.
4. The halogen-free epoxy resin composition according to any one of claims 1 to 3, characterized in that: The low dielectric curing agent includes any one or a combination of at least two of a benzoxazine curing agent, an active ester curing agent, an acid anhydride curing agent, a phenolic resin curing agent, an amine curing agent, a carboxylic acid curing agent, a cyanate curing agent, a benzoxazine curing agent or a maleimide curing agent; Preferably, the benzoxazine resin includes any one of bisphenol A benzoxazine, bisphenol F benzoxazine, bisphenol S benzoxazine resin, DDM benzoxazine resin, ODA benzoxazine resin, phenolphthalein benzoxazine resin or DCPD benzoxazine resin, or a combination of at least two thereof; Preferably, the anhydride curing agent is selected from any one of the following formula I or formula II or a combination of at least two thereof: Wherein, n:x=1:1 to 8:1; Preferably, the active ester curing agent is selected from any one or a combination of at least two of the active esters having the following structure of Formula III or Formula IV: In III, X is phenyl or naphthyl, j is 0 or 1, k is 0 or 1, and n represents a repeating unit of 0.25 to 1.25; In IV, m, n, and q are independently integers of 1 to 6, X is phenyl or naphthyl, and Y is the following group: Where K is 0 or 1.
5. The halogen-free epoxy resin composition according to any one of claims 1 to 4, characterized in that: The average particle size of the boron nitride is 2-20 μm.
6. The halogen-free epoxy resin composition according to any one of claims 1 to 5, characterized in that: The halogen-free epoxy resin composition further comprises other fillers; Preferably, the other filler is selected from any one or a combination of at least two of aluminum hydroxide, composite silica, fused silica, talc, boehmite, zeolite, wollastonite, magnesium oxide, calcium silicate, calcium carbonate, clay or mica; Preferably, the median particle size of the other fillers is D50=1.8-4.4 μm, and the maximum particle size is D100=5.0-20 μm; Preferably, the physical form of the other fillers may be flake, rod, sphere, hollow sphere, granule, fiber or plate; Preferably, the content of other fillers in the halogen-free epoxy resin composition is 40 to 200 parts by weight; Preferably, the phosphorus-containing flame retardant is selected from reactive phosphorus-containing flame retardants and / or additive phosphorus-containing flame retardants; Preferably, the reactive phosphorus-containing flame retardant is a compound containing phosphorus element and reactive groups; Preferably, the reactive groups include amino groups and / or phenolic hydroxyl groups; Preferably, the reactive phosphorus-containing flame retardant comprises a phosphorus-containing phenolic resin; Preferably, the additive phosphorus-containing flame retardant includes any one of tris(2,6-dimethylphenyl)phosphine, 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphophananthrene-10-oxide, 2,6-bis(2,6-dimethylphenyl)phosphinobenzene, 10-phenyl-9,10-dihydro-9-oxa-10-phosphophananthrene-10-oxide, phosphazene compounds or phosphates, or a combination of at least two thereof; Preferably, the halogen-free epoxy resin composition further comprises a curing accelerator; Preferably, the curing accelerator is selected from any one of imidazole accelerators, pyridine curing agents, Lewis acid curing agents, amine curing agents, phenolic curing agents, cyanate compounds or active ester compounds, or a combination of at least two thereof.
7. A resin glue, characterized in that: The resin glue is obtained by dissolving or dispersing the halogen-free epoxy resin composition according to any one of claims 1 to 6 in a solvent.
8. A prepreg, characterized in that: The prepreg comprises a base material and the halogen-free epoxy resin composition according to any one of claims 1 to 6 attached to the base material after being impregnated and dried.
9. A metal foil-clad laminate, characterized in that: The metal foil-clad laminate comprises at least one prepreg according to any one of claims 1 to 6 and a metal foil coated on one side or both sides of the stacked prepreg.
10. A printed circuit board comprising at least one of the prepreg according to claim 8 or the metal foil clad laminate according to claim 9.